Analysis of the correlation between the quality of school services and parental satisfaction at SDN Serua Indah 02, Tangerang Selatan - Efendi, Yarsi; Hapsari, Ratna F; Wulansari, Desi K; Inayati, Dinda Nurul (CAHAYA PENDIDIKAN, 2025)
This research aims to investigate the relationship between the quality of school services and its impact on parental satisfaction at SDN Serua Indah 02, Ciputat, Tangerang Selatan, Indonesia. The study seeks to provide a deeper understanding of the factors that influence parental satisfaction within the educational context. The study employs a quantitative survey method, utilising a questionnaire as the primary data collection instrument. The sampling technique, guided by Slovin's formula, yielded a total of 178 parents as respondents. Analysis was conducted using Pearson Product Moment correlation tests to measure the relationship between the quality of school services (including the dimensions of tangibility, reliability, responsiveness, assurance, and empathy) and parental satisfaction. The results of the research indicate a significant positive correlation between the quality of school services and parental satisfaction (r = 0.624, p < 0.05). The dimensions of tangibility and reliability were found to contribute most significantly to parental satisfaction, while the dimension of empathy highlighted the importance of individual attention to students' needs. The limitations of this research are associated with its narrow focus on a single school, which may restrict the generalisability of the findings to broader contexts. Future research should consider additional factors that may influence parental satisfaction across various educational settings. Implication of this research are school should focus on enhancing the quality of its services, actively engaging parents, providing staff training, and conducting continuous evaluations. These measures are essential for fostering strong relationships, improving parental satisfaction, and bolstering the institution's reputation in the field of education Keywords: Educational Service Quality, Parent’s Student Satisfaction, SDN Serua Indah 02 Tangerang Selatan, SERVQUAL Dimension